mutation and familial pediatric acute lymphoblastic leukemia: A case report - JinFang Zhang; MingYan Zhong (SAGE Open Medical Case Reports, 2024)
Hereditary factors contribute to the pathogenesis of pediatric leukemia. However, few studies have reported gene mutation pathopoeias. This paper reports genetic mutations associated with hereditary acute lymphoblastic leukemia. We reported a case of siblings diagnosed with acute lymphoblastic leukemia when aged 3 and 7 years, both siblings are alive after chemotherapy, and whole exome sequencing analysis was performed on the siblings and their parents. It was observed that both siblings had diheterozygous mutations in PML gene ( PML , NM_033250, exon7, c.2170A > G, p.S724G; PML , NM_033250, exon7, c.2195G > T, p.G732V), and their parents had heterozygous mutations in one mutation site of PML gene, respectively, suggesting that the diheterozygous mutations of PML gene might be causal genetic genes for the occurrence of acute lymphoblastic leukemia.